On the causes of mass extinctions - Bond, David P.G.; Grasby, Stephen E. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
The temporal link between large igneous province (LIP) eruptions and at least half of the major extinctions of the Phanerozoic implies that large scale volcanism is the main driver of mass extinction. Here we review almost twenty biotic crises between the early Cambrian and end Cretaceous and explore potential causal mechanisms. Most extinctions are associated with global warming and proximal killers such as marine anoxia (including the Early/Middle Cambrian, the Late Ordovician, the intra-Silurian, intra-Devonian, end-Permian, and Early Jurassic crises). Many, but not all of these are accompanied by large negative carbon isotope excursions, supporting a volcanogenic origin. Most post-Silurian biocrises affected both terrestrial and marine biospheres, suggesting that atmospheric processes were crucial in driving global extinctions. Volcanogenic-atmospheric kill mechanisms include ocean acidification, toxic metal poisoning, acid rain, and ozone damage and consequent increased UV-B radiation, volcanic darkness, cooling and photosynthetic shutdown, each of which has been implicated in numerous events. Intriguingly, some of the most voluminous LIPs such as the oceanic plateaus of the Cretaceous were emplaced with minimal faunal losses and so volume of magma is not the only factor governing LIP lethality. The missing link might be continental configuration because the best examples of the LIP/extinction relationship occurred during the time of Pangaea. Many of the proximal kill mechanisms in LIP/extinction scenarios are also potential effects of bolide impact, including cooling, warming, acidification and ozone destruction. However, the absence of convincing temporal links between impacts and extinctions other than the Chicxulub-Cretaceous example, suggests that impacts are not the main driver of extinctions. With numerous competing extinction scenarios, and the realisation that some of the purported environmental stresses may once again be driving mass extinction, we explore how experimental biology might inform our ...